CALL Communities and Culture – Short Papers From EUROCALL 2016 2016
DOI: 10.14705/rpnet.2016.eurocall2016.605
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-assisted language learning community and culture in French-speaking Belgium: the teachers’ perspective

Abstract: This paper focuses on the perceptions and uses of mobile technologies by 118 Belgian teachers in foreign language teaching and learning in secondary education. The purpose of the study is to analyze the teachers' attitudes towards the use of mobile technologies in-and outside the classroom via an online questionnaire. The preliminary findings presented in this paper establish that the concept of a 'Mobile-Assisted Language Learning (MALL) community' does not yet exist in our context as the use of mobile device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The investigation should continue as Van de Vyver (2016) suggested that deeper analyses of teachers as well as students perceptions of MALL will lead to the identification of the most influential factors that affect the use of mobile devices in a language classroom. The results of a preliminary showed that almost one hundred percent of vocational students had a gadget.…”
mentioning
confidence: 99%
“…The investigation should continue as Van de Vyver (2016) suggested that deeper analyses of teachers as well as students perceptions of MALL will lead to the identification of the most influential factors that affect the use of mobile devices in a language classroom. The results of a preliminary showed that almost one hundred percent of vocational students had a gadget.…”
mentioning
confidence: 99%